ANALYSIS OF THE READINESS OF TELAGA BUNDA HOSPITAL BIREUEN INRESPONDING TO FLOODS AND EARTHQUAKE DISASTERS: THE HOSPITAL SAFETY INDEX (HSI) APPROACH - Aris Winandar; Sri Wahyuni (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Acute Respiratory Infections, post-disaster epidemics, and infrastructure damage following hydrometeorological and seismic disasters in Aceh during 2025-2026 have placed enormous pressure on health facilities. Hospitals in disaster-prone regions such as Bireuen District must be assessed for their preparedness using validated instruments. This study aims to analyze the disaster preparedness level of Telaga Bunda Hospital Bireuen in facing flood and earthquake disasters using the Hospital Safety Index (HSI) approach developed by WHO/PAHO. The research employed a descriptive evaluative design using mixed methods, combining HSI self-assessment of 145 items across three modules (structural safety, non-structural safety, and emergency and disaster management) with structured observation, document review, and focus group discussions involving the hospital disaster team. Results indicated that Telaga Bunda Hospital Bireuen achieved a Safety Index of 0.78, categorized as Class A (the hospital is likely to function during and after a disaster). Module 2 (structural safety) scored 0.81, Module 3 (non-structural safety) scored 0.79, and Module 4 (emergency management) scored 0.74. The majority of indicators were rated as high safety level, particularly for structural integrity, electrical backup systems, and clinical staff readiness. Recommendations focus on strengthening disaster simulation drills, improving evacuation signage, and enhancing inter-agency coordination with BPBD Bireuen and Health Service.